Diversity Best Paper Awards for 2015 - Wink, Michael (Diversity, 2015)
Diversity is instituting annual awards to recognize the most outstanding papers in the areas of biological, genetical, chemical or environmental diversity published in Diversity. [...]
Gesehen am 02.07.2020